Analysis and Verification of a Slope Steering Model of TRVs in Hilly and Mountainous Environments - Luojia Duan; Kaibo Kang; Shiying Chen; Zixing Du; Longhai Zhang; Zhijie Liu; Fuzeng Yang; Zheng Wang (Agronomy)
Compared to wheeled vehicles, tracked robotic vehicles have less ground pressure, greater traction adhesion, and stronger climbing and obstacle crossing capabilities, making them suitable for agricultural production in hilly areas. Good steering performance directly relates to the mobility performance and operating efficiency of tracked robotic vehicles. Affected by the ground slope, the ground pressure distribution of the vehicle’s two tracks is uneven, leading to changes in its steering performance. Therefore, analyzing and researching the steering performance of a tracked robotic vehicle under sloped conditions is of great significance. This study establishes a slope steering model for tracked robotic vehicles based on a ground pressure model of the multi-peak varying amplitude cosine distribution and the shearing displacement relationship between the track and the ground, and analyzes the impact of vehicle structural parameters, road surface parameters, and steering parameters on steering performance. To verify the proposed theoretical model, multi-body dynamics software is utilized for simulation modeling and analysis. Turning tests on different slopes are conducted on a “soil–machine–crop” integrated experimental platform. The relative error between the numerical analysis results and the virtual simulation software’s results is less than 12%, and the relative error between the numerical analysis results and the experimental results is less than 10.3%; the good consistency between the theoretical results and the simulation’s results and the experimental results indicates that the model is, indeed, correct and effective. The established steering model can provide a theoretical basis for the design and control of new steering mechanisms for agricultural tracked robotic vehicles.